2006
DOI: 10.1111/j.1365-2672.2006.02953.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of water activity, temperature and solutes on the growth rate of P. italicum Wehmer and P. digitatum Sacc.

Abstract: In vitro effects of water activity, temperature and solutes on the growth rate of P. italicum Wehmer and P. digitatum Sacc. IntroductionCitrus fruits are generally stored in temperatures ranging from 0 to 7°C and relative humidities from 85% to 90%. During their storage, fruits are affected by several decays (Brown and Miller 1999). Penicillium digitatum Wehmer and P. italicum Sacc. are the main postharvest pathogens of citrus fruits, responsible, respectively, for green and blue decay. In turn massive spore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 26 publications
(60 reference statements)
5
18
0
Order By: Relevance
“…1a). This result was in agreement with that reported by Lahlali et al (2006) and Plaza et al (2003) who found that the optimum growth of P. italicum was at 25°C. Growth was greatest at temperature ranging from 20 to 25°C on Valencia late oranges (Fig.…”
Section: Temperature Effect On the In Vitro And In Vivo P Italicum Gsupporting
confidence: 83%
See 3 more Smart Citations
“…1a). This result was in agreement with that reported by Lahlali et al (2006) and Plaza et al (2003) who found that the optimum growth of P. italicum was at 25°C. Growth was greatest at temperature ranging from 20 to 25°C on Valencia late oranges (Fig.…”
Section: Temperature Effect On the In Vitro And In Vivo P Italicum Gsupporting
confidence: 83%
“…Generally, whatever the studied conditions, growth rates increased with an increase in temperature and the optimum temperature for growth was observed at 25°C, as previously reported by Lahlali et al (2006), Plaza et al (2003) and Lacey (1989). The effect of temperature on the in vitro and in vivo radial growth rates of P. italicum can be fitted by the following quadratic equations respectively: -0.014 T 2 + 0.56 T-1.36 and -0.017 T 2 + 0.637 T-0.33).…”
Section: Temperature Effect On the In Vitro And In Vivo P Italicum Gsupporting
confidence: 68%
See 2 more Smart Citations
“…Fungal spore germination is highly vulnerable to strobilurin fungicides, kresoxim-methyl, and trifloxystrobin, which are typically broadly active against almost all fungi, particularly when they are applied early as a preventative measure. Additionally, these two fungicides are considered to be lower-risk fungicides than conventional fungicides due to their low mammalian toxicity and benign profile toward avian species, though they negatively affect aquatic species (Plaza et al 2002;Lahlali et al 2006).…”
Section: Kresoxim-methyl Methyl(e)-methoxyimino[α-(o-tolyloxy)-o-tolmentioning
confidence: 99%